Waterproofing of porous carbonate rocks: Efficiency-controlling its properties - Esbert, R. M.; Alonso Sánchez, José (Materiales de Construcción, 1995)
The aim of this study is to establish which physical properties may be used, in a routine way, in order to know the efficacy rate of a treatment applied on a specific rocky substrate.Whit this purpose, two types of carbonated rocks, the limestone of Hontoria (Burgos) and the dolomite of Laspra (Asturias) have been chosen, with a very different configuration of their porosity systems. Three protection products, with silico-organic nature and widely used have been used, to wit: two siloxenes and a copolymer.Tue properties chosen (contact angle and water vapour permeability) have been the proper ones in order to determine the efficacy level of the different treatments. This level was demonstrated to be conditioned by the chemical characteristics of this product, and the influence of the characteristics is practically null.Other investigations are being carried out with the same rocks and treatment products in order to establish the corelationships between the efficacy rate of these treatments and the durability of the rock-treatment systems.